Improving Inclusivity in Robotics Design: An Exploration of Methods for Upstream Co-Creation - de Saille, Stevienna; Kipnis, Eva; Potter, Stephen; Cameron, David; Webb, Calum J. R.; Winter, Peter; O’Neill, Peter; Gold, Richard; Halliwell, Kate; Alboul, Lyuba; Bell, Andy J.; Stratton, Andrew; et al. (Frontiers in Robotics and AI, 2022)
Disabled people are often involved in robotics research as potential users of technologies which address specific needs. However, their more generalised lived expertise is not usually included when planning the overall design trajectory of robots for health and social care purposes. This risks losing valuable insight into the lived experience of disabled people, and impinges on their right to be involved in the shaping of their future care. This project draws upon the expertise of an interdisciplinary team to explore methodologies for involving people with disabilities in the early design of care robots in a way that enables incorporation of their broader values, experiences and expectations. We developed a comparative set of focus group workshops using Community Philosophy, Lego Serious Play and Design Thinking to explore how people with a range of different physical impairments used these techniques to envision a 'useful robot'. The outputs were then workshopped with a group of roboticists and designers to explore how they interacted with the thematic map produced. Through this process, we aimed to understand how people living with disability think robots might improve their lives and consider new ways of bringing the fullness of lived experience into earlier stages of robot design. Secondary aims were to assess whether and how co-creative methodologies might produce actionable information for designers (or why not), and to deepen the exchange of social scientific and technical knowledge about feasible trajectories for health-social care. Our analysis indicated that using these methods in a sequential process of workshops with disabled people which incorporated engineers and other stakeholders at the Design Thinking stage could potentially produce technologically actionable results to inform follow-on proposals.